Guarantees for the protection of the taxpayer’s legitimate interest: a paradigm shift - Sergey A. Yadrikhinskiy (Правоприменение)
The subject. The article is devoted to the analysis the dominant scientific conception, related legal problems and a new model of ensuring the implementation of the legitimate interest of the taxpayer.The purpose of the article is to consider the legal and organizational aspects in the field of ensuring the legitimate interests of taxpayers. The hypothesis of the study is that the level of guarantees for the implementation of the taxpayer's legitimate interests, as permitted, by its legal nature should not be inferior to subjective rights. The traditional view of the guarantees of legitimate interests in practical terms is unproductive, which forces a paradigm shift.The methodological basis of the study consists of various general (analysis, synthesis, comparative method, description) and special methods of cognition of the phenomena of legal reality. Among them, particularly significant are the legal-dogmatic and comparative legal methods.The main results and scope of their application. In domestic legal science there is a conceptual point of view that legitimate interests, regardless of industry affiliation, are guaranteed only in general or to a certain extent. At the same time, the jurisprudence of interests in the tax sphere is much more complex in nature than it is presented in the general theory of law.Through the prism of the features of public relations, traditional approaches to determining the mechanism of guaranteeing legitimate interest are subjected to critical analysis. Based on the needs of practice, a fundamentally new view on security instruments, the place and role of tax officials in the implementation of the legitimate interest is proposed. The point of view of the inferiority of the "warranty degree" guarantee degree of legitimate interests is substantiated, since such selectivity disorients both the taxpayer and the law enforcement agent (courts, tax authorities).Conclusions. It is concluded that the protective parity of subjective rights and legitimate interests of the taxpayer. In the new paradigm, the duty and responsibility of tax officials will act as guarantees for the implementation of the legitimate interests of taxpayers.